2017
DOI: 10.21608/ejbo.2017.944.1076
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides Production and Characterization from Marine-Derived Penicillium commune KP942881.1 with Some Medical Potential Applications

Abstract: 1HNMR analysis of EPS exhibited the presence of β-galatopyranosyl. The HPLC chromatography showed that the EPS consist of two peaks; raffinose and rhamnose. EPS showed antiproliferative activity at dose 10 mg/ml where the percentage inhibition of tumor viability cells of colon was 85%. In breast cell (Mcf-7), EPS inhibited 87% of the tumor cells at dose 10 mg/ml and also the antiviral activity of EPS of P. commune exhibited 22.8% inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In addition, a total of 48 bioactive compounds from different species of the genus Penicillium (nine of fourteen articles), including arenicolin A, isopenicin A, penipacids A, and norverrucosidin, were detected, showing the lowest IC 50 values against HCT-116 (7.3 μg/mL), SW-180 (0.74 μg/mL), RKO (8.4 μg/mL), and HCT-116 cells (5.7 μg/mL), respectively. Furthermore, isopenicin A induced apoptosis and modulated proteins involved in cell cycle progression from G2 to M [ 21 , 29 , 30 , 52 , 53 , 55 , 57 ]. The anti-tumor activity of some of the extracts and bioactive compounds from the genus Penicillium were tested against breast, cervix, and liver cancer cells, obtaining similar results [ 21 , 32 , 52 , 53 , 55 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a total of 48 bioactive compounds from different species of the genus Penicillium (nine of fourteen articles), including arenicolin A, isopenicin A, penipacids A, and norverrucosidin, were detected, showing the lowest IC 50 values against HCT-116 (7.3 μg/mL), SW-180 (0.74 μg/mL), RKO (8.4 μg/mL), and HCT-116 cells (5.7 μg/mL), respectively. Furthermore, isopenicin A induced apoptosis and modulated proteins involved in cell cycle progression from G2 to M [ 21 , 29 , 30 , 52 , 53 , 55 , 57 ]. The anti-tumor activity of some of the extracts and bioactive compounds from the genus Penicillium were tested against breast, cervix, and liver cancer cells, obtaining similar results [ 21 , 32 , 52 , 53 , 55 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, isopenicin A induced apoptosis and modulated proteins involved in cell cycle progression from G2 to M [ 21 , 29 , 30 , 52 , 53 , 55 , 57 ]. The anti-tumor activity of some of the extracts and bioactive compounds from the genus Penicillium were tested against breast, cervix, and liver cancer cells, obtaining similar results [ 21 , 32 , 52 , 53 , 55 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Exopolysaccharides were hydrolyzed in accordance with the procedure of Abou Zied et al [22]. The filtrate's carbohydrate content was examined using HPLC, Smart Line, Knauer, Germany.…”
Section: Hplc Analysismentioning
confidence: 99%
“…Similarly, Li et al 94 1)), showed antiproliferation activity on MCF-7 cells while the IC 50 was 550 μg mL −1 . 95 Generally, at present there is not much research reporting the polysaccharides from marine microorganisms and their anticancer activities on breast cancer. However, different polysaccharides from marine microorganisms might supply new anticancer agent candidates for breast cancer, so further research is needed.…”
Section: Polysaccharides From Marine Bacteria and Fungi And Their Ant...mentioning
confidence: 99%
“…Similarly, Li et al 94 also indicated that for the exopolysaccharide from Aspergillus terreus composed of [→3)-α- d -Manp(1→], [→6)-α- d -Manp(1 →] and [→2,6)-α- d -Manp(1→] with [α- d -Manp-(1 → 2)-α- d -Manp(1→] and [α-D-Manp-(1→] as branches substituted at the C-2 position of [→2,6)-α- d -Manp(1→], incubated with MCF-7 cells, the inhibition rate was only 25.5% and 30.6%, respectively, for 24 h and 48 h. Another exopolysaccharide from Penicillium commune consisting of raffinose and rhamnose, 2,6-di- O -substituted galactofuranose (2,6)-Galf-(1), and terminal glucopyranose (Glcp-(1)), showed antiproliferation activity on MCF-7 cells while the IC 50 was 550 μg mL −1 . 95 Generally, at present there is not much research reporting the polysaccharides from marine microorganisms and their anticancer activities on breast cancer. However, different polysaccharides from marine microorganisms might supply new anticancer agent candidates for breast cancer, so further research is needed.…”
Section: Polysaccharides From Marine Bacteria and Fungi And Their Ant...mentioning
confidence: 99%